Minimal invasive management of generalized peritonitis as a result of spontaneous ureteral rupture - Gobinath, S.; Rajendra, S.; Balagobi, B.; Gobishangar, S.; Jenil, A.; Varothayan, S. (Elsevier, 2023)
Introduction and importance: Generalized peritonitis following proximal ureteral rupture is a very rare compli- cation. This is about a successfully managed case without open surgical intervention. Case presentation: A lady in her 70s presented with generalized abdominal pain, high spiking fever and low urine output for 3 days. She was haemodynamically unstable on admission and was resuscitated and managed at intensive care unit. CECT abdomen revealed partial anterior ureteral rupture with pyonephrosis. She was managed with percutaneous nephrostomy and subsequent anterograde stenting. Her recovery was uneventful and follow up imaging revealed no features of malignancy. Clinical discussion: Generalized peritonitis due to renal pathology is very rare and it can be due to urolithiasis or neoplasm. Retroperitoneal infections may lead to irritation of peritoneum or fistulation into the peritoneum leading to generalized peritonitis. This can be managed by various surgical and non-surgical management modalities. Conclusion: There are various pathological causes for acute abdomen. One of the rare causes is spontaneous rupture of ureter in pyonephrotic kidney which can also be managed successfully with minimal intervention.
Keywords: Pyonephrosis; Spontaneous rupture; Peritoneal fistula; Peritonitis; Minimal invasive management